The Opportunity of Analysing Global Career - Szondi, Réka (International Journal of Engineering and Management Sciences, 2018)
The study aims to define global career and to present an applicable method. Internationalisation and globalisation indisputably have affect on companies actions. The value of human capital as a resource has got notably higher than before. To retain competitiveness, multinational companies have to focus their sight on employees with globally usable knowledge. In today’s globalized world international assignments are particularly frequent. It is a must to differentiate between working abroad willingly or sent abroad by the company. Achieved and applied knowledge from international assignments are essential ingredients of global career. However, the inappropriately planned career structure can cause damage for the company and for the cost effectiveness of the HR department. It is vital to appoint the most suitable employee for the assignment, to increase the company’s success rate and to maximize the individual’s performance as soon as possible. The effectiveness of the selection has influence on performing a successful assignment in the process of the career path.